Penerapan SCM Terhadap Pengendalian Persediaan Barang Pada PD. Makro Market Menggunakan PHP - Deny Hidayatullah; Dadi Hamdani; Dede Suandi (NUANSA INFORMATIKA, 2010)
Application of SCM (Supply Chain Management) in the company is essential for controling inventory. By applying the method of SCM, the company will be better because the scope of SCM is a system in which business organization distributes goods production and services to its customers. The chain of this supply is also a network of interconnected organizations that have same goal i.e distributing Â goods to users well. Information systems developed in the application of SCM is to control inventory in PD. Macro Market. It is an integrated system between the parties directly associated with PD. Macro Market, including suppliers, PD. Macro Market and customers. The company gives access for suppliers to view the minimum stock of inventory so that inventory control is not only monitored by the company but also by the supplier. While on the customers side, customers can see the availability of the goods so that customers will easily place an order because there has been the availability of goods. The customers are not bothered to Â come to PD. Macro Market to make a reservation because this system allows customers to make reservations online